Uso De Geogebra Y Su Incidencia En El Proceso EnseÃ±anza- Aprendizaje De Grafica De Funciones En El Nivel Superior - Marcelo, Coronel Maji Franklin; Rodrigo, Guilcapi Mosquera Jaime; Mario, Vargas Guambo Juan (European Scientific Journal, ESJ, 2018)
The objective of the research was to determine the incidence of the use of GeoGebra in the learning process of graph of functions of the subject of Mathematics 1 in the students of the first semester of the School of Electronic Engineering in Telecommunications and Networks of the Polytechnic School of Chimborazo. The research is bibliographic, descriptive and quasi-experimental, to which a hypothesis to be demonstrated was proposed. A curricular plan was considered which was developed by a control group (traditional method - 38 students) and an experimental group (use of GeoGebra - 37 students). The groups were evaluated in 2 parts, in the (Pre) and (Post) phases through an evaluation rubric composed of different activities. An intervention plan was applied for the experimental group that allowed to establish an improved scenario to the traditional one. The obtained data from each group represented the academic performance, which was tabulated, analyzed and interpreted. Finally, the results were subjected to a Ztest, which allowed to determine the use of GeoGebra as an academic support tool that has a positive impact on the teaching-learning process of representation of the results of the graphs of functions.